Analysis Study of Backing Plate's Strength and Braking Temperature to Failure Modes of Composite Brake Block on Coach and Wagon - DELANIS SEMBIRING (NIM 13104070), HARSA
One of the main public transportation for land strip is train. The main system that supports safety and comfort on train is braking system. In a braking system, brake block is one of the most important things. Needs of train brake block in Indonesia is fulfilled by metallic brake block and composite brake block. Compared with metallic brake block, composite brake block has several advantages such as: (1) lighter, so that composite brake block is easier to be installed, (2) low wear rate, (3) longer life cycle, and (4) better ratio of price and life cycle. Composite brake block often gets fail in passenger coach and wagon. Generally, failure occurs on composite brake block with backing plate's structure that not strong enough for bending load and effect of excessive braking temperature. In this research, composite brake block material has been tested. On this experiment modelling and simulation of backing plate and composite brake block has been developed using ANSYS 11 software to analyze the effect of backing plate's strength and braking temperature to brake block failure modes. The result shows that backing plate with grove profile stronger than flat backing plate to withstand deflection at bending tensile load. Failure of composite brake block caused by maximum tensile load due to bending. Thermal crack occur when friction coefficient over 0.22 with maximum velocity of 90 km/h for coach, while for the wagon the failure occur when the coefficient friction more than 0.20 with maximum velocity 60 km/h in flat railways.